A superconducting magnetic energy storage with dual functions of active filtering and power fluctuation suppression for photovoltaic microgrid. (June 2021) - Jin, Jian Xun; Wang, Jian; Yang, Ruo Huan; Zhang, Tian Long; Mu, Shuai; Fan, Ying Jun; Xing, Yun Qi
Highlights: The superconducting magnetic energy storage (SMES) based on shunt active power filter (SAPF) provides an integrated protection for harmful currents and power fluctuations in photovoltaic (PV) microgrid, which makes the cost of SAPF-based SMES more economical as a power system stabilizer. The modified i p − i q method combining instantaneous reactive power theory and power decoupling control is proposed to extract reference current. The fuzzy logic control method is designed to maintain the DC-link voltage stability and reduce depth of discharge of SMES. Abstract: This paper proposes a superconducting magnetic energy storage (SMES) device based on a shunt active power filter (SAPF) for constraining harmonic and unbalanced currents as well as mitigating power fluctuations in photovoltaic (PV) microgrid. The AC side of the SAPF is interfaced to the point of common coupling (PCC), and its DC-link is with integration of a DC/DC converter and an energy storage superconducting coil (SC). A multi-objective control technique based on modified i p − i q method and hysteresis SVPWM is adopted to implement the dual functions of active filtering and power fluctuation suppression. A fuzzy logic control (FLC) method is proposed for the DC/DC converter to stabilize the DC-link voltage and reduce the discharging depth of the SMES. The single and comprehensive performances of the SAPF-based SMES in various scenarios have been attested through a series of comparisons based on a conventional SAPF and a SAPF-based battery energy storage (BES). The superiority and robustness of the proposed FLC method are identified through simulation comparisons with a classical proportional-integral controller and a sliding mode controller in various scenarios considered.